Formation of effective product distribution channels as a logistic systems economics component of agricultural complex of Ukraine - Shishkin, Viktor; Pavliuk, Tetiana; Polusmiak, Yuliia; Sushchenko, Oleksandr (Management and Entrepreneurship: Trends of Development, 2022)
The article highlights the essence of distribution channels and considers management aspects of sales channels formation and development for the Ukraine agro-industrial complex. Problems and main factors of influence on the logistics system formation of the agroindustrial enterprise with effective trade channels of national agricultural products are analyzed. Today, in the process of realizing the geopolitical advantages of the national economy, it is worth paying attention to the potential of the national agro-industrial complex, which is the main budget-forming sector of the national economy of Ukraine. One of the key vectors of development for Ukraine’s integration into the world economy is the formation of effective channels for distributing products of national agricultural producers to export markets. The participation in world trade may open opportunities for our country to enter a new stage of development. JEL Classification: A22, I20, I21.